Proyecto de Factibilidad para la creación de un cine en el Cantón Catamayo de la Provincia de Loja - Sanchez Avila, Mayra Alejandra (2016)
The subject of this thesis was developed with the aim of making the "PROJECT FEASIBILITY FOR THE CREATION OF A FILM IN CANTON CATAMAYO Loja province" with a purpose of covering the existing unmet demand in Canton. Some objectives were formulated. For which an investigation was applied to the population of catamayo canton so a survey was conducted and a sample of the same resulting of 381 respondents was obtained it develops. In the market study it determined: that the potential demand is 85.56%, while the actual demand has a 96.91%, an average per capita consumption of 23 services used per year of which in turn effective demand is obtained 93.61%. On the technical study it found that working 100% of the installed capacity will be offered to 91,520 services a year, but for the first year only 60.24% of the installed capacity will be used. Within the technical study it took into account research in market research in order to find the optimal size of the film that is 234 m ^ 2, which will be used for adaptation and implementation unmet demand; For year one is 73,216 people, with an optimal rate of 80% of capacity used, an unmet demand of 151,938, which will be covered in full capacity utilization is 100% is determined. The film will be located in the San Jose neighborhood catamayo canton of the Province of Loja. he Administrative Study, structural and functional organization, the film is determined by adding to its legal basis, philosophical basis and its specific 6 functions, the organization in which it is directed to each of the departments of management, administrative department distributed and financial, marketing department and technical department. Regarding the financial study determines is needed to invest in fixed assets $ 110,682.69 in deferred assets and $ 3.716.84 for a month of operations needed $ 7.788.33 in current assets, giving a total investment of $ 122.187.86; plus the selling price of each service worth $ 1.90 for the first year, multiplied by the number of times attending the movies are $ 73.216,00 gives us an income of $ 139,110.40, in the state was obtained gains and losses in the first year of a liquid $ 13.863,97 utility will be obtained. By the results obtained it can be said that the breakeven in year one occurs when the company works with an installed capacity of 78.70% and income on sales of $ 109,480.72 at this point the company covers with its revenue expenditure total. The financial evaluation the result of NPV resulted in $ 90.816,36 the result of IRR of 34.58%, the benefit cost is at $ 1.40, recovery of capital will be in 3 years, 7 months and 10 days and finally with the sensitivity analysis was determined that the project is not sensitive to an increase in costs by 10.4620% the same that allows for positive net flows and disminuciónón of its revenue from 7.499% maximum support generated positive net flows. The methodology used in this thesis project was the scientific, inductive, analytical method and survey techniques and direct observation and bibliography.